2017
DOI: 10.1007/s11356-017-0873-6
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid protects against radiation-induced testicular damage in male rats: impact on SIRT1 and PARP1

Abstract: Ionizing radiation is a major contributor to male infertility by destroying spermatogenesis. Therefore, the need for an effective radio-protective agent is evident. The objective of the present study was to investigate the potential radio-protective effect of ferulic acid (FA) on radiation-induced testicular damage. Mature male Sprague-Dawley rats were either exposed to a single-dose gamma radiation (5 Gy) and/or treated with FA (50 mg/kg), daily for 7 days before irradiation. Sirtuin1 (SIRT1), poly (ADP-ribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Moreover, de Boer et al (2006) stated that quercitin, a phenolic compound inhibits silent information regulators (SIRT1) activity due to its ability to form sIRT 1 inhibatory metabolites. This was in accordance with EL-Mesallamy et al (2018). Inhibition of sIRT1 decreases cellular resistance to oxidative stress, activates both NF_ kB & proinfilamatory cytokines and promotes cellular apoptosis (Chung et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, de Boer et al (2006) stated that quercitin, a phenolic compound inhibits silent information regulators (SIRT1) activity due to its ability to form sIRT 1 inhibatory metabolites. This was in accordance with EL-Mesallamy et al (2018). Inhibition of sIRT1 decreases cellular resistance to oxidative stress, activates both NF_ kB & proinfilamatory cytokines and promotes cellular apoptosis (Chung et al, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…Bars with different superscripts are significantly different at p ˂ 0.05 obviously stimulated SIRT1 expression in a dose-dependent and time-dependent manner. Similar effects were also observed in FA-treated skeletal muscle cells, bone, and testis [62][63][64]. Second, genetically knocking down SIRT1 robustly abolished FA-stimulated autophagy induction.…”
Section: Discussionsupporting
confidence: 61%
“…In animal studies, SIRT1 was reported to regulate acrosome biogenesis by modulating autophagic flux during spermiogenesis in mice (24). Recent findings revealed that ferulic acid protects male rats against radiation-induced testicular damage by increasing SIRT1 expression (25). Existing evidence indicates the importance of SIRT1 in the male reproductive system.…”
Section: Introductionmentioning
confidence: 99%